KEMAMPUAN BERPIKIR KRITIS SISWA MELALUI MODEL SNOWBALL THROWING BERBANTUAN GEOGEBRA PADA MATERI FUNGSI KUADRAT KELAS X-6 DI SMA NEGERI 1 PADEMAWU - Duwi Lusiyana Anggraini; Hasan Basri; Hairus Saleh (JES-MAT: Jurnal Edukasi dan Sains Matematika, 2025)
Grade X-6 students of SMA Negeri 1 Pademawu showed relatively low critical thinking ability in mathematics learning and struggled to understand quadratic function material because their previous conventional instruction lacked visual media. This study aimed to improve students' critical thinking ability by implementing the Snowball Throwing learning model assisted by GeoGebra. The researchers conducted Classroom Action Research (CAR) across two cycles involving 21 students, using student activity observation sheets, response questionnaires, and tests developed from operational critical-thinking indicators synthesized from Facione (2015), Ennis (2011), and Paul and Elder (2019). The results showed that student activity increased from 2.97 to 3.40, positive responses increased from 97.7% to 100%, and the average critical thinking score increased from 61.6 (pretest) to 70.6 (cycle I) and 80.7 (cycle II), with classical mastery reaching 81.8% and exceeding the 75% success indicator. These findings confirm that the Snowball Throwing model assisted by GeoGebra effectively improves students' activity, responses, and critical thinking ability in quadratic function material. Mathematics teachers are recommended to adopt this combined model as an alternative strategy for topics that require both visual representation and active reasoning.